2012
DOI: 10.1073/pnas.1202095109
|View full text |Cite
|
Sign up to set email alerts
|

Top-down attention switches coupling between low-level and high-level areas of human visual cortex

Abstract: Top-down attention is an essential cognitive ability, allowing our finite brains to process complex natural environments by prioritizing information relevant to our goals. Previous evidence suggests that top-down attention operates by modulating stimulus-evoked neural activity within visual areas specialized for processing goal-relevant information. We show that top-down attention also has a separate influence on the background coupling between visual areas: adopting different attentional goals resulted in spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
225
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(236 citation statements)
references
References 35 publications
9
225
2
Order By: Relevance
“…Stimulus-driven attention in the model might reflect enhanced communication between early and late visual cortical areas. This idea is supported by studies that demonstrated greater interarea correlations of activity between visual areas with attention (71)(72)(73)). An alternative, but not mutually exclusive, hypothesis is that attentional modulation is mediated by neural signals from frontoparietal cortices (74,75).…”
Section: Discussionmentioning
confidence: 72%
“…Stimulus-driven attention in the model might reflect enhanced communication between early and late visual cortical areas. This idea is supported by studies that demonstrated greater interarea correlations of activity between visual areas with attention (71)(72)(73)). An alternative, but not mutually exclusive, hypothesis is that attentional modulation is mediated by neural signals from frontoparietal cortices (74,75).…”
Section: Discussionmentioning
confidence: 72%
“…To examine intrinsic functional connectivity, we analyzed activity correlated with the aIFO seeds across a functional run after removing the effect of the task events. This type of approach has been used by others (Al-Aidroos et al, 2012) and shown to result in patterns of functional connectivity that closely resemble those calculated from "true" resting state scans (Grady et al, 2014;Grigg and Grady, 2010a).The functional connectivity pattern accounting for the most covariance in the data is shown in Figure 6a (p < 0.001). The spatial pattern of brain regions was similar to the set of regions with increased activity for errors ( Figure 2a) and to the common task-related functional connectivity pattern ( Figure 5a); indeed, there was considerable overlap among these three spatial patterns (Figure 7).…”
mentioning
confidence: 74%
“…To examine intrinsic functional connectivity, we analyzed activity correlated with the aIFO seeds across a functional run after removing the effect of the task events. This type of approach has been used by others (Al-Aidroos et al, 2012) and shown to result in patterns of functional connectivity that closely resemble those calculated from "true" resting state scans (Grady et al, 2014;Grigg and Grady, 2010a).…”
Section: Intrinsic Functional Connectivitymentioning
confidence: 96%
“…Therefore, both residual and resting-state spontaneous correlations largely reflect the intrinsic organization of PFC. Although task-evoked changes in largescale spontaneous correlations are relatively small, they are statistically reliable (12,35) and influence behavior (27,36). Moreover, context-dependent information processing is also supported by dynamic changes in large-scale task-evoked correlations (37)(38)(39).…”
Section: Discussionmentioning
confidence: 99%
“…S2). For each selected voxel, we then regressed out a model of task variables to produce an estimate of spontaneous activity and computed all pairwise time series correlations (12,27). We next used multidimensional scaling (MDS) to reduce the dimensionality of the spontaneous correlation structure and visualize its relationship to context preferences (Fig.…”
Section: Significancementioning
confidence: 99%